09 THE ROLE OF TUFT CELL SPECIFICATION AND FUNCTION IN INFLAMMATORY ILEITIS. (7th February 2019) - Banerjee, Amrita; Herring, Charles A; Simmons, Alan J; Kim, Hyeyon; McKinley, Eliot T; Chen, Bob; Vega, Paige; Liu, Qi; Coffey, Robert J; Lau, Ken S
Abstract: Background: Inflammatory Bowel Disease (IBD) and its subtype Crohn's disease (CD) arise due to a loss of tolerance to environmental antigens in genetically susceptible individuals. Longitudinal analysis of CD incidence has identified an inverse correlation between rates of communicable disease and autoimmune disorders, particularly in countries endemic for helminth infestation. A case report published by Broadhurst et al described the use of helminth eggs to treat an IBD patient with refractory disease. Induction of a type 2 immune response following helminth colonization promoted mucosal healing and achieved clinical remission. Epithelial tuft cells are responsible for orchestrating the type 2 immune response following helminth colonization via the release of the type 2 cytokine IL-25. In acute infection, tuft cells drive their own specification and tuft cell hyperplasia is a critical host response for worm extrusion. Therefore, modulation of tuft cell function may prove efficacious in CD treatment. Results: In a well-established mouse model (TNF ΔARE ) of Crohn's-like ileitis, we observed highly inflamed regions with lower tuft cell numbers, while less inflamed regions had more Dclk1+ tuft cells, suggesting an inverse correlation between inflammation and tuft cell specification. We applied p-Creode, a novel trajectory mapping algorithm, to single-cell RNA sequencing datasets in order to investigate tuft cell specification in wildtype and TNF ΔARE animals. Contrary to previously published literature, p-Creode demonstrated that epithelial tuft cells are specified outside of the canonical secretory lineage. We then developed a novel, genetically-inducible model of tuft cell hyperplasia (Lrig1 CreERT2/+ ; Atoh1 fl/fl – AtohKO), where the loss of the master secretory regulator Atonal Homolog 1 ( Atoh1 ) drove increased tuft cell numbers in the in vivo small intestine. However, recombination of Atoh1 in ex vivo small intestinal enteroids did not induce tuft cell hyperplasia. Similarly, broad-spectrum antibiotic treatment of AtohKO animals suppressed tuft cell hyperplasia, implicating a role for the microbiome in driving tuft cell specification in the absence of eukaryotic infection. Our novel findings suggest that commensal microbial-derived metabolites in the AtohKO model are capable of driving tuft cell hyperplasia, independent of helminth colonization. Future Directions & Impact: We will identify species and metabolite changes that are responsible for driving tuft cell hyperplasia independent of helminth colonization. Understanding tuft cell specification and function could enable us to better leverage this rare and elusive cell type to modulate inflammatory symptoms in IBD.